Early onset of care needs in the older population: The protective role of housing conditions. (May 2023) - Cartagena Farias, Javiera; Brimblecombe, Nicola; Hu, Bo
Abstract: Most older people wish to live in their own homes as they age and to have a choice over their housing and care situation. Housing has the potential to play a key role in promoting independence, delaying and/or preventing the onset of care needs and in influencing the level and type of care provision required. However, many older people live in homes that are not suitable for their comfort and needs. Our study focuses on older people living in non-specialist housing in England and aims to i) explore how housing characteristics cluster; and ii) investigate their association with an early onset of care needs. We used four waves of a large representative longitudinal sample of people aged 50 or over, covering the period 2012 to 2020. We performed Latent Class Analysis and a Cox regression survival model to provide answers to our research questions. We found that people living in poor housing conditions or living in social rented housing are more likely to experience early onset of care needs, which may lead to a higher demand for, and utilisation of, long-term care services. We believe that gaining a better understanding of the relationship between housing-related conditions and care needs is paramount from the preventative and service provision point of view, and is of relevance to policymakers, practitioners, and current and future adult long-term care users. Highlights: The 3 typologies of housing were identified may require different strategies to raise standards. Those living in poor housing are more likely to experience early onset of care needs. People privately renting or in social housing are more likely to have an early onset of care needs. The combination of housing conditions may have an effect on when care needs start to develop. Improving housing quality offers an opportunity to prevent the development of care needs.